Addressing the gap in health data management skills: an online self-guided course for researchers and health professionals - Naomi Waithira; Brian Mutinda; Kehkashan Shah; Evelyne Kestelyn; Susan Bull; Liam Boggs; Trudie Lang; Phaik Yeong Cheah (BMC Medical Education)
Abstract Background The healthcare sector is rapidly evolving with the rise of digital technology and data-driven decision-making. However, traditional medical education has yet to fully integrate training on managing health-related information, resulting in a significant skills gap among medical and research professionals. This gap is pronounced in low- and middle-income countries (LMICs), where data privacy concerns and inadequate infrastructure hinder efforts to utilise and share health data. Aims To address this gap, we developed an online, modular course aimed at providing foundational skills on capturing, storing and sharing health data. Methods The course was developed using the ADDIE(Analyze, Design, Develop, Implement, Evaluate) instructional design model. A needs assessment workshop involving 25 global health proffesionals identified key training gaps which informed the curriculum’s development. A multidisciplinary team from six institutions developed the modules. The course was piloted in a face-to-face setting with 37 participants and later adapted for online delivery via the Global Health Network platform. We evaluated the course using Level 1 of Kirkpatrick’s model for training evaluation. Results Six foundational modules were developed: Introduction to Data Management, Data Quality, Data Repositories, Ethics of Data Sharing, Data Governance, and Costing for Data Management. Between December 2020 and April 2024, 6,384 individuals from 90 countries completed the course. Of these, 32% were from Africa, 15% from Asia, 16% from South/Central America and the Caribbean, and 24% from Europe. Summative evaluations, based on voluntary post-module surveys, demonstrated high relevance to participants’ learning needs (96.6%) and strong intentions to apply the skills gained (88.3%). Key motivators for enrollment included the course’s free access, relevance to professional or academic needs, and trust in the organizations and authors behind the content. Conclusions The high enrolment and broad geographical reach demonstrates the potential of online training as a cost-effective tool to equip health practitioners and researchers with data literacy skills. Future evaluations will assess its impact on participants’ knowledge, behavior, and data-sharing and reuse practices.